Analysis of the Willingness to Pay for Organic Fruits and Vegetables in the Matara and Galle Districts in Southern Province, Sri Lanka - Rasanjalee, P. H. N.; Silva, K. N. N. (University of Jaffna, 2024)
Growing fruits and vegetables organically can be introduced as an eco-friendly farming type. Promoting the consumption of organic fruits and vegetables is very useful to improve healthy lifestyles among Sri Lankan citizens. Producing high-quality fruits and vegetables by using nature-friendly farming practices without harming the environment is the main concept of organic farms. There are numerous factors that affect the consumer’s willingness to pay for organic fruits and vegetables. Recently, Sri Lankans have been eager to buy organic fruits and vegetables due to their health concerns. The present study is conducted to analyze the preference patterns and the willingness to pay for organic fruits and vegetables in the Matara and Galle districts of the Southern province of Sri Lanka. A sample of forty five organic fruits and vegetables consumers in the Galle and Matara districts was selected for the study due to limited resources. A structured questionnaire was used to collect data from consumers of organic fruits and vegetables. The SPSS software package was used to analyze the data. Descriptive statistical methods and Chi- Square test were used to analyze the data. According to the analysis of the study, the highest percentage, 88.9% of the respondents, are willing to pay higher prices for organic fruits and vegetables. Furthermore, most respondents (97.7%) prefer to buy organic fruits and vegetables from a separate organic marketplace. According to the study, most of them prefer organic fruits and vegetables with the intention of achieving a healthy and long life. Due to the data limitation of this research, it can be suggested to the Sri Lankan government to give more attention to conducting more research on the organic fruit and vegetable market island-wide in the future.
Keywords: Organic fruits; Organic vegetables; Preference; Willingness to pay